PENGARUH PROFITABILITAS, INTENSITAS MODAL, DAN INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK - Margaretha Amandha Cahyamustika; Rachmawati Meita Oktaviani (Jurnal GeoEkonomi, 2024)
Because tax money is so vital to a state's budget, tax policy has taken on new significance.. Tax avoidance refers to measures made by filers to reduce their taxable income. This study uses a five-year data set (2018-2022) to examine how companies in the consumer non-cyclical sector of the IDX fare in terms of tax avoidance in relation to their profitability, capital intensity, and inventory intensity. In this research, 180 samples were chosen through the purposive sampling method, applying specific criteria for sample selection. Quantitative analysis is conducted by employing multiple linear regression analysis. The research findings indicate that there is a negative influence between profitability and tax avoidance, a positive influence between capital intensity and tax avoidance, and no influence between inventory intensity and tax avoidance. Keywords: Tax avoidance; Profitability; Capital Intensity; Inventory Intensity